PENGARUH PADAT TEBAR YANG BERBEDA TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis niloticus) DENGAN MENGGUNAKAN FILTER DASAR - Ramadayanti, Andini; Ahmad, Nasir; Zulkhasyni, Zulkhasyni; Pardiansyah, Dedi; Andriyeni, Andriyeni (University of Prof. Dr. Hazairin, SH, 2021)
This research was conducted from May to July 2020 at the Laboratory of the Faculty of Agriculture, Prof. Dr. Hazairin, SH Bengkulu for 50 days. The purpose of this study was to determine the stocking density of Tilapia (Oreochromis niloticus) on the growth of Tilapia cultivated in plastic containers using a basic filter. The design used was a completely randomized design (CRD), which consisted of 4 experiments and 4 replications in order to obtain 16 experimental units, namely P1 (stocking density 40 fish / m2), P2 (stocking density 50 fish / m2), P3 (stocking density 60 fish / m2), P4 (stocking density 70 fish / m2) with a size of 8 -12 cm. The results showed that stocking density had an effect on growth in absolute length and absolute weight but had no effect on feed conversion, feed efficiency and survival. The best density is in the stocking density of 60 individuals / m2 with a survival rate of 92.0%. By using a basic filter during the research, you can maintain water quality where dissolved oxygen in the water at the beginning of the maintenance of dissolved oxygen is 6.4 (ppm) - 6.8 (ppm) to 6.0 (ppm) - 6.8 (ppm), temperature ranges from 25 oC - 29 oC, and pH ranges from 6.8 – 7.